ANALYSIS QUALITY OF E-LEARNING INSTITUTE OF CHRISTIAN RELIGION TARUTUNG STATE (IAKN) ON USER SATISFACTION USING WEBQUAL 4.0 METHOD - Frans Denni Immanuel Sinaga; Iin Seprina (Institute of Computer Science (IOCS), 2022)
The web is a complete data provider and is an important aspect in various fields, especially learning because it can be accessed without limits and is easy to use. This research certainly has the aim of achieving the value of user satisfaction and finding the factors that affect the quality of the E-Learning website. To support this research, researchers carried out observations, similar literature research, interviews and questionnaires as a collection of research information. In this research, the quality of the IAKN Tarutung E-learning web was measured using the Webqual 4.0 procedure. The source of information for this research was obtained through a questionnaire processed from IAKN Tarutung students with a population of 2828 and illustrations of 350 respondents. As a result, research can be stated that web quality simultaneously influences the creation of user satisfaction. On the other hand, partially webqual size is information and usability does not significantly affect user satisfaction. This means that data size and usability must be increased again so that user satisfaction can be created better.